Dental Schools Vacant Budgeted Faculty Positions, Academic Year 2014–15. Issue 8 (1st August 2016) - Wanchek, Tanya; Cook, Bryan J.; Slapar, Franc; Valachovic, Richard W.
Abstract : Every year the American Dental Education Association (ADEA) surveys U.S. dental schools on their faculty workforce. The ADEA Survey of Vacant Budgeted Faculty Positions gathers information on vacancies, sources of new hires, and reasons for separations. This report, which highlights trends from the 2014–15 academic year, allows assessment of faculty workforce developments over time and across schools. For this report, 63 out of 65 U.S. dental schools provided data, for a 97% response rate. The results showed that the rise in full‐time vacancies that occurred during the past few years continued as the economy recovered from the recent recession. Given the large number of faculty members who came from private practice (n=483) or left their positions for private practice (n=185), the private sector appeared to continue to be an attractive alternative with which dental schools must compete. Nonetheless, schools were typically able to fill vacant positions within a year. The primary obstacle to filling vacant positions related to the ability of schools to offer sufficient compensation to attract qualified applicants. Schools did not have many lost positions (n=16) relative to new positions to be filled (n=82), suggesting an expansionary trend among dental schools. Overall, there continued to be a need for more faculty members, but that demand was not significantly greater than in prior years.